EFFECTIVENESS OF ORAL MEDICATIONS IN THE PERIOPERATIVE PERIOD OF ROTATOR CUFF INJURIES - SYSTEMATIC REVIEW - Edivando de Moura Barros; Elzir Finizola Costa Junior; Fabio Teruo Matsunaga; Milla Pompilio da Silva; Eiffel Tsuyoshi Dobashi; Marcel Jun Sugawara Tamaoki (Acta Ortopédica Brasileira)
ABSTRACT Postoperative pain management remains a significant challenge in patient care, being particularly crucial in the context of arthroscopic or open rotator cuff repairs. Objective: To compare the effectiveness of different medications in controlling pain after this surgical intervention. Material and methods: A systematic review of the literature was carried out, conducting a data search in the Pubmed/Medline, Science Direct and Embase databases. Initially, 1,223 articles were identified where, after detailed analysis, eight studies were selected to compose this research. The total sample comprised 703 patients. Results: We observed a predominance of male participants in most studies, and the age range of those involved varied, on average, from 50.0 to 59.9 years old. The studies included cover a variety of pain management strategies after arthroscopic rotator cuff repair, highlighting the diversity of approaches in the literature, including analgesics, anti-inflammatories, anticonvulsants and opioids. Conclusion: In general, we showed that the interventions used were well tolerated. Some studies have demonstrated mild adverse effects, such as nausea, vomiting, dizziness, headache and other transient symptoms. This systematic review highlights that there is no well-established protocol for managing postoperative pain in arthroscopic rotator cuff repair, comparing the effectiveness of different medications. The diversity of approaches observed in the literature highlights the need for personalized strategies. Despite the good tolerance and positive results of the interventions, the choice of medication must consider the individuality of the patient and specific characteristics of the procedure. Level of Evidence II; Systematic Review.